BOOK REVIEW ON JEFFREY EUGENIDES’ THE VIRGIN SUICIDES - Fauzia, Anisa (LANTERN (Journal on English Language, Culture and Literature), 2015)
Relation between parents and teenagers is very important. Parents have big influence to develop teenagers’ identity. As teenagers, they want to be more independent and decide their own way without parents’ interference. Meanwhile, some of parents will not agree with teenagers’ mind, they tend to be more protective to their teenagers. They will control what teenagers do and often forbid them to do what they want. It is because parents want to give the best thing for their teenagers. Although parents have a good reason why they are strict in their protection, teenagers will still feel restrained. Adolescence is a period when teenagers make their own decision, live independently and socialize with their peers. Therefore, when parents do not understand what teenagers want, there will be misunderstanding between parents and teenagers.